(untitled) (International Journal of Environmental Sciences, 2025)
This study presents a smart, sensor-integrated fire exposure simulation system, meticulously designed around the Arduino Mega 2560 platform, to evaluate the thermal and structural resilience of concrete and mortar materials under severe fire conditions. The system is engineered in compliance with Indian and international fire testing standards such as IS 3809:1979, IS 1641:1960, IS 1642:1989, ASTM E119, and ISO 834. The heart of the hardware configuration is the Arduino Mega 2560, selected for its high input/output pin count, sufficient memory space, and compatibility with various analogue and digital sensors. Each sensor is chosen based on performance, reliability, and compatibility with real-time data acquisition. Type-K thermocouples are used to monitor internal concrete temperature gradients up to 1200°C. IR/UV flame sensors ensure burner activity is continuously tracked, while MQ-series sensors detect combustible gas leaks, ensuring safety during simulation. The MPX5700 pressure sensor monitors gas line pressure to detect malfunctions, and the max6675 Thermocouple module IR sensor captures non-contact surface temperatures of the test specimens. Real-time sensor data is displayed through a serial interface and LED module, and provisions have been made for data logging and future cloud-based remote monitoring through IoT integrations. The entire system logic was simulated in Proteus software, and the operational sequences were validated using physical experiments. Simulated results and hardware tests confirmed the successful triggering of actuators and alerts based on sensor outputs. The proposed automated fire exposure simulation system bridges the gap between cost-effective hardware and high-standard fire resilience testing. It contributes significantly to the evolution of smarter and safer civil infrastructure while promoting innovation in engineering education and disaster mitigation research